Analytical Matrix of the Characteristic of Life Cycle of Political and Administrative Elite - Vladimir Nicolaevich Kolesnikov; Andrey Vladimirovich Samusevich (Управленческое консультирование)
The article deals with the circulation of elites, describes the concept of the life cycle of the elite, its content as a tool of political analysis, to determine the spatial and temporal scope of the development cycle. The main result in terms of substantive content of the category «life-cycle of the political elite» is amodel for determining the functional state of the elite in the form of a generalized matrix variable life cycle analysis of the political elite. This article is disclosure of performance’s theses at the forum of Young Political Scientists VII Russian Congress of political scientists RAPS (Moscow, November, 19-21, 2015).